Modelos matemáticos e computacionais para descrever a transmissão de dois sorotipos de vírus de dengue - Vilches, Thomas Nogueira [UNESP] (2015)
We present a model of ordinary differential equations to describe the dengue transmission in a human and a mosquito populations when there are two serotypes of circulating virus. Analytic and numeric results to the equilibruim points of this model, and the study of the stability of this points were obtained. We assume the quasi-steady state approach to the mosquito population, in order to study and compare the dynamics of transmission of two serotypes of dengue virus in networks with different topologies. We consider the transmission model through complex networks with different degrees of conectivity among the individuals and, thus, it provides a better representation of the social interations. We observe that the transmission dynamics of dengue depends strongly on the network topology and the mean number of conections, thus the control measures must have a different impact given the diversity of conections among the individuals on the population